Parameterised design of robust point‐to‐point fast motion controller - Wentao Yu; Guoyang Cheng (Electronics Letters)
A dual‐parameter design of expanded proximate time‐optimal controller is proposed for fast point‐to‐point motion in typical electromechanical servo systems with a damping element. The controller initially resorts to a saturated control signal for the fastest acceleration or braking if possible and then seamlessly gives way to a linear control strategy once the motion slows down. The damping ratio and natural frequency of the linear control law are chosen as the design parameters to allow for a better tuning of the control performance. An extended‐state observer is also included for simultaneous estimation of system speed and disturbance. Experimental verification is conducted on a DC motor position servo system using a TMS320F28335 board, and the effectiveness of the proposed design is demonstrated.